Measuring the Job Satisfaction of Female Library Professionals Working in the Health Libraries in Dhaka City - Sultana, Farzana; Begum, Bilkis (Eastern Librarian, 2012)
Job satisfaction is an important area to determine the view of the library professionals towards their job in the library. The study has been under taken to measure the level of job satisfaction of female health library professionals in Dhaka city and how do the job facets (MSQ, 1967) affect on job satisfaction of female health library professionals. There is a cross sectional observational study to see the level of job satisfaction among health library professionals. A standard questionnaire (MSQ, 1967) is used to measure the level of job satisfaction of the sample. The result shows that out of twenty job facets eleven facets are highly significant for the job satisfaction and nine facets quite insignificant for job satisfaction. The study shows independence, variety of work, social status of the job, supervision-human relation supervision-technical, moral values, authority, ability utilization, library policies and practices, scope of advancement, relation with co-workers, recognition of job done and achievement has significant effect on job satisfaction. Further more it noticed females are less satisfied at their job. Finally, the significant recommendations have been put forth to improve the level of job satisfaction of female health library professionals in Bangladesh. DOI: http://dx.doi.org/10.3329/el.v23i1.12117 Eastern Librarian Vol.23(1) 2012 pp.37-50